1988
DOI: 10.1097/00004032-198812000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Sugar as an Emergency Populace Dosimeter for Radiation Accidents

Abstract: This paper briefly describes a report which has been developed to enable protective action guidance to be determined for transportation accidents involving radioactive material. The protective action guide uses data from on-scene observations as input to a series of simple flow charts leading to protective action recommendations. Where the necessary data is unavailable or unknown, the guide uses the assumptions and results found in the authors' worst case hazards analysis report.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…The intensity of the sucrose signal in the sample spectrum increased proportionally up to 20 kGy. It has been reported that the intensity of ESR signals of crystalline sucrose increases in proportion to the absorbed dose (Nakajima, 1988). In this study, the intensity of ESR signals from sucrose in irradiated plant materials also corresponded well to the absorbed dose.…”
Section: Identification Of Esr Spectral Components and Determination supporting
confidence: 79%
“…The intensity of the sucrose signal in the sample spectrum increased proportionally up to 20 kGy. It has been reported that the intensity of ESR signals of crystalline sucrose increases in proportion to the absorbed dose (Nakajima, 1988). In this study, the intensity of ESR signals from sucrose in irradiated plant materials also corresponded well to the absorbed dose.…”
Section: Identification Of Esr Spectral Components and Determination supporting
confidence: 79%
“…The behavioral characteristics of radical species derived from fructose, glucose and sucrose were similar. The high stability of radicals in crystalline saccharides obtained by radiation, such as mono-or disaccharides, is well known (Nakajima, 1988). Very similar behavior of radicals in UV-irradiated mono-saccharides in air and in an atmosphere of nitrogen has been reported (Kashiwagi and Enomoto, 1981).…”
Section: Esr Spectral Characterizations Of Carbohydrates Radicalsmentioning
confidence: 83%
“…6 mT apart. In addition, the generation of carbohydrate radicals, including sucrose and cellulose, increases in proportion to absorbed dose (Nakajima, 1988;Yamaoki et al, 2009;Yordanov and Georgieva, 2004). The ESR analysis of absorbed dose focused on stable carbohydrate radical components in spectra from irradiated plants material is expected to result in high quantitative performance.…”
Section: Identification Of Radical Components In Irradiated Gingersmentioning
confidence: 99%
“…The possibility to use table sugar for retrospective EPR dosimetry was investigated by Nakajima (1988), Nakajima and Otsuki (1990), Trivedi and Greenstock (1993), Fattibene et al (1996) and others. Tchen et al (1993) examined different binders for sucrose pellets production and determined that 40% of sucrose in an inert silicone elastomer allow to measure doses in the range 0.5-10 Gy with a standard uncertainty 74%.…”
Section: Introductionmentioning
confidence: 99%